KREATIF matematika 4-6 tahun Kak-Seto ... [et al.] ; editor, Mila Rachmawati, Margaretha H. Eddy ; ilustrasi, Suryaman - Kak-Seto; Rakhmawati, Mila; Eddy, Margaretha H; Suryaman (Erlangga, 2005)
64 hlm ilus 28 cm